Exploring the Future of Smart Homes: Voice Control Technologies and Applications - Navneet Kaur; Pragati Prajapati; Preet Sahu; Suryansh Jain; Vivek Kumar Rai (International Journal of Electrical Machine Analysis and Design, 2024)
With the use of voice commands, smartphones, and the Internet of Things, homeowners may utilise an intelligent house automation system, a technology-driven solution, to control and automate a variety of home systems and gadgets from a central hub. The system typically includes equipment such as smart thermostats, smart lighting, smart locks, security systems, and entertainment systems. With the increasing prevalence of IoT, smart homes have become increasingly popular, and automation systems have emerged as a key technology for controlling and managing various home appliances and systems. The system work with the multiple language like {English, Hindi} This note explores an exhaustive detail of the present state of automation systems for smart homes and aims to identify areas for future research and development along with comfort, energy efficiency, privacy, and accessibility that a smart home automation system offers users can enhance their life as a whole. The current paper also highlights the components of smart home automation system but also put a spotlight on application and challenges associated with it.
Keywords: Home Automation; Raspberry Pi; electrical and electronic devices; energy conservation; physically challenged; portability